Titik Temu Pemikiran Mahmoud Mohamed Thaha dan Abdullahi Ahmed An-Na'im - Khoir, Tholkhatul (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2016)
Abdullahi Ahmed an-Na'im is deeply influenced by the Islamic Reform Movement in Sudan pioneered by Mahmoud Mohamed Taha. Together with other Taha supporters, an-Na'im formed a sociopolitical community that became famous for Tahaism. This article wants to show how the relationship of the two minds is so close and how Islamic legal thought of an-Na'im is partially influenced by Taha. In terms of historical research methodology, it can be said that Taha is a history of idea for an-Na'im. This is because the thought of an-Na'im turns out to be the same as Taha in terms of the importance of the naskh, and differs in worship, mysticism, socialism, and public reason. Moreover, the underlying power of the theorem an-Na'im is not merely an individual, not of individual processes aware of its importance in the flow of thought, but rather of the collective goals of a group that underlie individual thought. Most of his thoughts cannot be properly understood as long as their relation to life or to the social implications of human life are not taken into account.—Abdullahi Ahmed an-Na‘im sangat terpengaruh oleh Gerakan Reformasi Islam di Sudan yang dipelopori oleh Mahmoud Mohamed Taha. Bersama sama dengan para pendukung Taha lainnya, an-Na‘im membentuk sebuah komunitas sosial politik yang kemudian terkenal dengan Tahaisme. Artikel ini ingin menunjukkan betapa hubungan pemikiran keduanya sangat dekat dan betapa pemikiran hukum Islam an-Na‘im sebagiannya dipengaruhi oleh Taha. Dalam istilah metodologi penelitian sejarah, dapat dikatakan bahwa Taha adalah history of idea bagi an-Na‘im. Hal ini karena pemikiran an-Na‘im ternyata sama dengan Taha dalam hal pentingnya naskh, dan berbeda dalam hal ibadah, tasawwuf, sosialisme, dan public reason. Selain itu, kekuatan yang mendasari sikap teoritis an-Na‘im bukan semata merupakan sesuatu yang individual semata, yakni tidak berasal dari proses individu menyadari kepentingannya dalam arus pemikiran, akan tetapi lebih berasal dari tujuan-tujuan kolektif suatu kelompok yang mendasari pemikiran individu. Sebagian besar pemikirannya tidak dapat dimengerti secara tepat selama kaitannya dengan kehidupan atau dengan implikasi sosial kehidupan manusia tidak diperhitungkan.